Chemical synthesis of Nd2Fe14B/Fe–Co nanocomposite with high magnetic energy product. Issue 51 (1st October 2021) - Ngo, Hieu Minh; Lee, Gyutae; Haider, Syed Kamran; Pal, Umapada; Hawari, Thomi; Kim, Kyung Min; Kim, Jongryoul; Kwon, Hae-Woong; Kang, Young Soo
Abstract : Nd2 Fe14 B is one of the most popular permanent magnets (PMs) possessing the best energy product (BH)max among the common PM materials. Abstract : Nd2 Fe14 B is one of the most popular permanent magnets (PMs) possessing the best energy product (BH)max among the common PM materials. However, exchange-coupled nanocomposite magnets fabricated by embedding nanostructures of soft-phase magnetic materials into a hard-phase magnetic matrix manifest higher remanence and a higher energy product. Here we present the fabrication of exchange coupled Nd2 Fe14 B/Fe–Co magnetic nanocomposites using gel-combustion and diffusion–reduction processes. Pre-fabricated CoFe2 O4 nanoparticles (NPs) of ∼5 nm diameter were incorporated into a Nd–Fe–B oxide matrix during its synthesis by gel-combustion. The obtained mixed oxide was further processed with oxidative annealing at 800 °C for 2 h and reductive annealing at 900 °C for 2 h to form a Nd2 Fe14 B/Fe–Co nanocomposite. Nanocomposites with different mol% of soft-phase were prepared and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and physical property measurement system (PPMS) to study their crystalline phase, morphology and magnetic behavior. Addition of 7.7 mol% of soft-phase was found to be optimum, producing a coercivity ( H c ) of 5.6 kOe and remanence ( M r ) of 54 emu g −1 in the nanocomposite.